‘On Not Eating Rice Whilst Grieving’: An Exploratory Study on The Relationship Between Me Ro’ Death Ritual And Self-Management - Wuryaningrat, Nikolas Fajar; Sumual, Tinneke E.M.; Karinong, Klauria; Apituley, John (Humaniora, 2023)
Me ro' tradition mandates families of a recently deceased person to abstain from consuming rice and entering rice fields until the deceased is buried. However, executing this tradition is considered challenging due to rice’s position as staple food with religious significance. Furthermore, the difficulty of adhering to Me ro' lies in the virtue of self-management of the family members. This exploratory study uses an observational method and in-depth interviews to collect information. Triangulation, involving documentation, recording, and peer-reviewed sources, is employed to ensure the validity, impartiality, and ethicality of the information. Two elders from Simbuang Village and two students who are originally from the village, but have studied outside of Simbuang Village serves as the informants of this study. The result of this study reveals Me ro' tradition to require stringent procedures, social sanctions, and economic obligations, which renders it to be challenging to fulfil. Moreover, to successfully accomplish Me ro', it depends on psychological, social, existential determinants, and lifestyle factors. Therefore, practicing Me ro' is not solely contingent on individual self-discipline, but also relies on the community's involvement to encourage, motivate, and supervise the Me ro' practice. In conclusion, it relies upon individual’s self-management and the community's ability to collectively support and supervise in the procedures.